Optimasi Portofolio dengan Lexicographic Goal Programming pada Bursa Efek Indonesia - Nilam Purnama Sari; Muhammad Subhan; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2021)
Abstract – A portfolio is a collection of investment opportunity that aims to select a combination of efficient of shares owned, in the form of profit (return) is optimal in forming the optimal portfolio, there are three criteria that must be considered, maximizing the total funds that, maximizing expected return, minimizing risk market (systematic risk coefficients). One model that can solve this problem is lexicographic goal programming. research purposes is how to obtain a stock portfolio optimation with lexicographic goal programming and the proportion of the funds invested. The method used is descriptive method that analyzes the theories related to lexicographic goal programming. The result obtained is an optimum portfolio.Keywords – investment, portfolio, return, the coefficient of systematic risk, lexicographic goal programming